Identifying and managing CAR T-cell–mediated toxicities: on behalf of an Italian CAR-T multidisciplinary team. (4th March 2022) - Martino, Massimo; Macheda, Sebastiano; Aguglia, Umberto; Arcudi, Luciano; Pucci, Giulia; Martino, Bruno; Altomonte, Maria; Rossetti, Antonio Maria; Cusumano, Giuseppa; Russo, Letteria; Imbalzano, Lucrezia; Stelitano, Caterina; et al.
ABSTRACT: Introduction: Chimeric antigen receptor (CAR)-T-cell therapy is a new treatment for patients with hematologic malignancies in which other therapies have failed. Areas covered: The review provides an overview for recognizing and managing the most acute toxicities related to CAR-T cells. Expert opinion: The development of immune-mediated toxicities is a common challenge of CAR-T therapy. The mechanism that determines this toxicity is still unclear, although an unfavorable tumor microenvironment and a pro-inflammatory state put patients at risk. The monitoring, diagnosis, and treatment of post-CAR-T toxicities must be determined and based on international guidelines and internal clinical practice. It is urgent to identify biomarkers that can identify patients at greater risk of developing complications. The adoption of consistent grading criteria is necessary to improve toxicity management strategies continually. The first-line therapy consists of supportive care and treatment with tocilizumab or corticosteroids. An early start of cytokine blockade therapies could mitigate toxicity. The plan will include cytokine release prophylaxis, a risk-adapted treatment, prevention of on-target/off-tumor effect, and a switch on/off CAR-T approach.